Measurement of Sound Absorption Coefficient (SAC) and Transmission Loss (TL) in Cement-Bonded Particleboard Made from Coconut Coir - Rohny Setiawan Maail; Lydia Riekie Parera (Green Engineering: International Journal of Engineering and Applied Science, 2025)
This study aims to analyze the acoustic characteristics of coconut-fiber-based Cement-Bonded Particleboard (CBPB) through measurements of the Sound Absorption Coefficient (SAC, α) and Transmission Loss (TL). CBPB samples were fabricated with thickness variations of 12, 16, and 20 mm and tested using an impedance tube in accordance with ISO 10534-2:1998 for SAC and ASTM E90-09 (2016) for TL measurements. The study examined the effect of panel thickness on sound absorption and transmission loss across a frequency range of 125–4000 Hz. The results showed that the α value increased with both frequency and panel thickness, reaching a maximum of 0.78 at frequencies of 2500–3150 Hz for the 20 mm panel. The TL measurements indicated that the highest transmission loss reached 42 dB at a frequency of 4000 Hz. These findings suggest that thicker CBPB panels provide better acoustic performance, both in absorbing sound and reducing transmission. Overall, coconut-fiber-based CBPB demonstrates strong potential as an eco-friendly structural acoustic material suitable for applications in sustainable building design, interior partitions, and noise control solutions.